Longitudinal gait assessment in a stiff person syndrome. Issue 4 (December 2018) - Schirinzi, Tommaso; Sancesario, Andrea; Romano, Alberto; Favetta, Martina; Gobbi, Marina; Valeriani, Massimiliano; Bertini, Enrico S.; Castelli, Enrico; Vasco, Gessica; Petrarca, Maurizio; Della Bella, Gessica
Abstract : Stiff person syndrome (SPS) is an autoimmune disorder with multiple clinical presentations, all characterized by generalized or focal muscular stiffness leading to abnormal postures and movements. To date, no standardized treatments are available; also, the outcome measures are mainly clinical based and unstandardized, limiting the reliability of clinical trials. In this case study, we used the eight-camera motion capture system for gait analysis (GA) to outline the gait features and track the clinical evolution of a young patient with SPS receiving a personalized multimodal therapy. GA was accurate in reflecting clinical changes over a 7-week-long period, thus representing a potential source for objective biomarkers in SPS. Therefore, future studies focusing on either the natural history or the treatment of SPS could adopt GA for reliable outocome measures, confirming this preliminary observation.